Continuous-wave operation of far-infrared quantum cascade lasers - Ajili, Lassaad; Scalari, Giacomo; Hofstetter, Daniel; Beck, Mattias; Faist, Jérôme; Beere, Harvey; Davies, Giles; Linfield, Edmund; Ritchie, David (My University, 2002)
Continuous-wave operation of a terahertz quantum cascade laser is reported. Optical output powers ranging from 410 µW at 10 K to 124 µW at 35 K, at an emission wavelength of 66 µm are obtained.